2015
DOI: 10.14202/vetworld.2015.388-392
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella spp. from chevon, mutton and its environment in retail meat shops in Anand city (Gujarat), India

Abstract: Aim:The aim of this study was (i) To attempt isolation and identification of Salmonella species from samples. (ii) Serotyping of Salmonella isolates. (iii) Detection of virulence factor associated genes by polymerase chain reaction (PCR).Materials and Methods:A total of 284 samples comprised of chevon and mutton (112 samples each) as well as 60 samples (20 each of retail meat shops environment samples viz. Butchers’ hands, knives and log swabs) were collected from the retail meat shops in and around Anand City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
1
8
4
1
Order By: Relevance
“…Some studies reported the detection of this gene in all tested Salmonella spp. isolates [49][50][51][52][53][54][55][56][57][58]. On the other side, Moussa et al [59] and Maysa and Abd-Elall [60] couldn't find invA gene in all isolates, same as our study.…”
Section: Resultssupporting
confidence: 83%
“…Some studies reported the detection of this gene in all tested Salmonella spp. isolates [49][50][51][52][53][54][55][56][57][58]. On the other side, Moussa et al [59] and Maysa and Abd-Elall [60] couldn't find invA gene in all isolates, same as our study.…”
Section: Resultssupporting
confidence: 83%
“…in goat carcasses slaughtered at retail shops of Parbhani city, Maharashtra where zero prevalence of Salmonella in goat samples was recorded [ 13 ]. A study from Anand, Gujarat recorded the incidence of Salmonella in chevon as (3.57%) [ 14 ]. Results of present finding also goes in parallel with the finding from Mumbai wherein workers reported the absence of Salmonella in mutton samples [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella species are Gram-negative facultative anaerobe bacteria and have been isolated from humans, animals, and the environment [8][9][10][11][12][13][14]. Salmonellae are among the major pathogenic bacteria in humans as well as in animals [15,16].…”
Section: Introductionmentioning
confidence: 99%